Hog cholera - Spaulding, Max Gilbert (My University, 1896)
Introduction: The disease popularly known as hog Cholera, is by no means so simple a melody as the name implies; and after many years of investigation, there is still a great deal of confusion with regard to the symptoms and causes as well as the various names by which the disease has been known, such as swine plague, swing fever, red soldier, purples and typhoid fever of swine. Scientists generally recognize two diseases, distinguished as hog cholera and swine plague, though these may occur together in any degree of complication.
Citation: Spaulding, Max Gilbert. Hog cholera. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Hog cholera; Disease; Investigation; Symptoms; Theses; Manuscripts (documents)